Optimization of extraction conditions of volatile compounds of roasted beef by solid-phase microextraction - Vanessa C. Francisco; Larissa C. Almeida; Stanislau Bogusz Junior; João Oiano Neto; Renata T. Nassu (Química Nova)
Aroma is one of the most important sensory attributes for acceptance by beef consumers. The first step in analysing the volatile compounds associated with this attribute is their extraction from the food matrix, solid-phase microextraction has been widely used for volatile compound determination in meat. This study aimed to test six different solid-phase microextraction (SPME) fibre coating materials for their volatile compounds extraction efficiency for roasted beef and to optimize the extraction conditions using response surface methodology. Gas chromatography coupled with a flame ionization detector (GC-FID) and mass spectrometry (GC-MS) were used. The choice of SPME fibre coating was based in the total area obtained by GC-FID analysis for the six fibre coatings. The optimum time and temperature for SPME extraction was 60 ºC/65 minutes. The mixed-phase fibre coatings showed the best results for extracting volatile compounds in roasted beef as higher number of compounds were identified. The carboxen/polydimethylsiloxane (CAR/PDMS) fibre extracted the largest number of compounds under the optimum extraction condition. Aldehydes were the predominant class of compounds found in roasted beef, followed by alcohols and hydrocarbons.